Rickettsia africae in the West Indies - Kelly, Patrick J. (Centers for Disease Control and Prevention, 2006)
Rickettsia africae is the agent of African tick-bite fever, a mild but common disease of local persons and tourists in Africa. The major vector of this spotted fever group rickettsia is most likely Amblyomma variegatum, the tropical bont tick, which has become widely distributed through the West Indies in the last 30 years. This report reviews all available information on R. africae in the West Indies.